A obra e o engajamento de Diamela Eltit : arte marginal e resistência política no Chile (1979-1989) - Isadora Bolina Monteiro Vivacqua (2019)
During Augusto Pinochet’s Military Dictatorship in Chile (1973-1990), the writer Diamela Eltit (1949-) stood out because of her strong political engagement through, especially, her cultural production. The purpose of the research is to analyze Eltit's intellectual trajectory, showing how she used art as a tool to report and resist against the violence and arbitrariness of the Chilean State. Our analysis is focused on two main points. First, we present the performance of the writer in the Colectivo Acciones de Arte (CADA), group founded by Eltit and four other intellectuals, responsible for the execution of important urban interventions, specially in Santiago – all of them bringing critical analysis to Pinochet’s regime. Furthermore, the group contributed to expand traditional art techniques to cultural productions, incorporating new methods and objects in their works, such as video-arts and performances. Our second focus of analysis referred to Eltit’s political engagement through her literary productions. We discuss three works published by her during this period – Lumpérica (1983); Por la patria (1986); El Padre mío (1989) – and the way how they were used as an instrument of political struggle. It’s important to highlight that in the first two mentioned books, there is a more specific accusation about opression lived by women in such context. In this way, the debate about gender issues is also another central point of our investigation. In order to deepen this theme and the writer's engagement, we also analyzed the Eltit's performance in feminist groups and her struggle for women's rights.